Women's studies centres in Europe community information and documentation - Stundžienė, Lijana (Information & Media, 1994)
The aim of this article is to describe the present state of women's information and documentation in Europe Community, to outline future exchange of information on women and gender in Europe. The difficulties involved in obtaining relevant information on women in mainstream documentation are also well-known. This has resulted in women establishing their own libraries, archives and documentation centres.The need for cooperation between all these institutions and co-ordination of their activities has been evident for a long time. Over the last 3 years, several initiatives have been taken to achieve this.There are presented many statistical data about book stocks, users number and so on.This article consists from 5 parts: information and documentation situation in Europe Community, general situation in EC, collections, catalogues, classification and indexing, users and producers, conclusion.In order to facilitate teaching and research in Women's Studies Vilnius University Women's Studies Centre is gradually increasing resources of the library with books, journals and other publications that are being issued in the world. Over the past year, the Centre has received many generous donations of books from publishers and individual libraries.Now library contains 1000 (one thousand) books. The dominant area is English, which accounts for 67% of all documents, 6% documents are in Lithuanian, other documents are in German, French, Italian. Library has 2 types of catalogues: index card catalogue and electronic catalogue. Index card catalogue is alphabetic according to the author's surnames. Systematic book catalogue is being created.In electronic book's catalogue searching is available according to: author name, title, publishing house name, publishing place, publishing year, language, UDK index, key word, ISBN number.The library is open to the public during office hours.
Keywords: -